2013
DOI: 10.1111/dsu.12215
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Peel Incorporating Triethyl Citrate and Ethyl Linoleate in the Treatment of Moderate Acne: A New Therapeutic Approach

Abstract: This therapy was effective and well-tolerated in all cases. Chemo-exfoliation sessions ensured the continuous monitoring of clinical results and improved patient quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, authors conclude that the efficacy of this lotion was based on the ability of linoleic acid in reducing the inflammation mediated by the neutrophils and the 5a‐reductase activity. In fact it has been demonstrated that linoleic acid downregulates neutrophilic oxygen metabolism and phagocytosis (Raone et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, authors conclude that the efficacy of this lotion was based on the ability of linoleic acid in reducing the inflammation mediated by the neutrophils and the 5a‐reductase activity. In fact it has been demonstrated that linoleic acid downregulates neutrophilic oxygen metabolism and phagocytosis (Raone et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, authors conclude that the efficacy of this lotion was based on the ability of linoleic acid in reducing the inflammation mediated by the neutrophils and the 5a-reductase activity. In fact it has been demonstrated that linoleic acid downregulates neutrophilic oxygen metabolism and phagocytosis (Raone et al, 2013). Use of this lotion containing triethyl citrate and ethyl linoleate could reduce the risk of antibiotic resistance also because HS is not a «classic» infectious disease: there is no unique bacterial agent but a polymorphic flora (Al-Hamamy, NoaimiI, Al-Turfy, & Rajab, 2015).…”
Section: Discussionmentioning
confidence: 99%